Factors Affecting Customer Loyalty: An Empirical Evidence from the Toll Road Industry in Indonesia - Denny Chandra Irawan; Yeshika Alversia (Bina Nusantara University, 2024)
Toll road rest areas are one of the main pillars of the toll road industry, and higher interest in buying at toll road rest areas is one of the keys to their financial success. The research aimed to identify and analyze the relationship between revisit intention and customer loyalty, as well as perceived price fairness, perceived satisfaction, and service quality. These variables were believed to be the main drivers for toll road users to make purchases at toll road rest areas. A statistical analysis approach was used with the Partial Least Square-Structural Equation Modelling (PLS-SEM) method for 573 respondents. They were consumers of the Trans Java toll road rest area. The survey was conducted directly on customers of the Trans Java toll road rest area at 15 locations. The results show that perceived price justice and satisfaction positively and significantly impact revisit intention. Then, revisit intention has a positive and significant impact on customer loyalty. Service quality has a positive and significant impact on perceived satisfaction and customer loyalty. The findings show that service quality, which is most strongly influenced by assurance, responsiveness, and empathy, is the main factor influencing customer loyalty. Based on the research results, the practical application is how managers can improve service quality, perceived price justice, and perceived satisfaction for price-sensitive consumers, who also tend to be sensitive to the service quality they get.